"Die Provinzen Bosnien und Herzegowina sollen von Österreich besetzt und verwaltet werden." - Der österreichisch-ungarische Einfluss auf das okkupierte/annektierte Bosnien-Herzegowina - Andreas Spornberger (Historia.scribere)
The Austrian–Hungarian Influence on Bosnia–Herzegovina After the Occupation 1878 This paper is about the Austrian–Hungarian influence on the occupied lands of Bosnia–Herzegovina from 1878 until the end of the Habsburgian rule in 1918. It examines exemplarily the innovation set in action in terms of economy, the educational system and - as it is a multicultural region -  the life of the jewish minority. As it will be shown, there were general changes in these fields and they differ depending on the examined issue.